Use of multimedia educational software in learning mathematics in a public educational institution in callao - Díaz Manrique, Jimmy (2021)
The present investigation has as general objective to determine the influence of the use of multimedia educational software in the learning of mathematics in a Public Educational Institution in Callao. The research design is quasi-experimental and applied in nature. The research is quantitative in focus. The study population comprises first grade high school students from the Callao District Educational Institution, for data collection of the variable use of multimedia educational software, the survey technique was applied and a questionnaire was used as an instrument. Likert scale, for the validation of this instrument the validation method of expert judgment was applied, by specialists in the field of education and Information and Communication Technologies, the results were averaged and a score of 89 was obtained, therefore that the experts indicate in consensus that the instrument is valid and applicable, the reliability of the instrument was determined by applying a pilot test and the data were analyzed through the internal consistency method and a Cronbach's alpha coefficient was obtained through value of 0.87; For the Mathematics Learning variable, the Mathematics assessment instrument was used, the reliability was determined through the KR20 reliability coefficient, the reliability coefficient is 0.94, with which we conclude that the instrument studied has high reliability. For the data processing, the student's T statistic was applied. The results obtained after processing and analyzing the data indicate that the general hypothesis presents a value in the t test of 0.0001 which is less than 0.05 (0.0001 <= 0.05) corresponds to the significance value, which indicates that the null hypothesis is rejected and the general research hypothesis is accepted that states that “The use of multimedia educational software influences the learning of Mathematics in students of a public educational institution in Callao.